A numerical optimization study of CdS and Mg0.125Zn0.875O buffer layers in CIGS-based solar cells using wxAMPS-1D package. (4th March 2022) - Hadjab, Moufdi; Wagner, Jan-Martin; Bouzid, Fayçal; Boudour, Samah; Hadj Larbi, Abderrahim; Bennacer, Hamza; Ziane, Mohamed Issam; Saeed, M A; Abid, Hamza; Berrah, Smail
ABSTRACT: The performance of copper indium gallium selenium (CIGS) based solar cells with cadmium sulfide (CdS) and magnesium zinc oxide (Mg x Zn1- x O) buffer layers has been investigated comparatively with the new version of a one-dimensional device simulation program for the analysis of microelectronic and photonic structures ( wx AMPS-1D). The structures of solar cells have been analysed keeping in view the effect of doping as well as of thickness of buffer and absorber layers. It is observed that the conversion efficiency and external quantum efficiency (EQE) are improved using Mg0.125 Zn0.875 O compound buffer layer for ZnO/Mg0.125 Zn0.875 O/CIGS structure to 22.01% and 89.7%, respectively, whereas the obtained conversion efficiency and EQE for ZnO/CdS/CIGS structure are 21.06% and 88.78%, respectively. The obtained results are in good agreement with the recently published work and the proposed structure of solar cells would have potential regarding improvements in the existing solar cell technology.